Goal, Role, Audience, Situation, Product, Standard (GRASPS) and It’s Implication to the Writing Skills in Filipino of Grade 10 Students - FAJA, CHARLIE (International Journal of Arts, Sciences and Education, 2025)
In the rapidly evolving field of education, the innovative and effective use of assessment strategies is crucial for enhancing students’ skills. This study aimed to determine the effectiveness of the Goal, Role, Audience, Situation, Product, Standard (GRASPS) framework as an authentic assessment strategy for improving the writing skills in Filipino of Grade 10 students at Esperanza National High School for the academic year 2024–2025. Using an experimental design, the study employed descriptive statistics, t-tests, and a five-point rating scale to analyze the data. The experimental group was assessed using the GRASPS framework for their written performance tasks, while the control group used traditional assessment methods. Writing performance was evaluated based on accuracy, logical organization, understanding of the topic, language style, and ability to persuade readers. Results showed that while both groups made significant progress, the experimental group exhibited a higher mean gain score in writing skills. This suggests that the choice of assessment strategy significantly influences student outcomes. Overall, the study concludes that GRASPS is an effective assessment strategy that positively impacts students' writing proficiency. The findings may serve as a basis for encouraging teachers to develop assessment tools that foster meaningful and performance-based learning experiences in writing.